FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN DEPOSITO BERJANGKA PADA BANK UMUM DI KOTA PEKANBARU - Riansyah '; Isyandi '; Rahmat Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the factors that influence the demand deposits at commercial banks in the city of Pekanbaru. This research uses quantitative study using multiple linear regression analysis with significance level of 5% (0,05), which was applied to the computer program SPSS version 18.0. in this study performed statistical tests (t-test and F test), test the partial correlation coefficients and multiple determination coefficient test. The results showed that together simultaneously (Test F) income, interest rates and education levels affect the amount of time deposits of 321.339% with a significance level of 0.000 and partially (t test) each also affect the amount of time deposits with the results of the equation Y = 6.107 -2,520+ + 41,334,323.616 - 2,527,578.183 . earnings effect amounted to 6.107 with a significance of 0.000, the interest rate also affects the amount of time deposits of 4.133 with 0.000 significance and impact of educational level - 2,527,578.183 with significance 0.335. The predictive ability of the four variables are the amount of deposits commercial banks is 90.9% ( = 0.909) as well as in the show by the magnitude of the adjusted , while the remaining 9.1% influenced by other factors were excluded from the study variables It can be concluded that the level of income, interest rates and the level of education has a significant influence on the amount of time deposits at commercial banks in the city of Pekanbaru. Any increase in the level of income, interest rates and levels of education will cause the amount of time deposits at commercial banks in Pekanbaru city will also increase.Keywords: income, interest rates, education levels, time deposits, commercial banks